2003
DOI: 10.1007/s00232-002-1042-4
|View full text |Cite
|
Sign up to set email alerts
|

Removal of the MDCK Cell Primary Cilium Abolishes Flow Sensing

Abstract: The hypothesis that cell primary cilium is solely responsible for the flow-induced Ca2+ response in MDCK cells was tested by removal of the cilia from mature, responsive cells. Incubation of the cells with 4 mM chloral hydrate for 68 hours resulted in the complete loss of the primary cilia and in disorganization of microtubules, as visualized by immunofluorescence. When intracellular Ca2+ concentration was measured with Fluo-4, the elevation that normally accompanies an increase in fluid flow was abolished aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
253
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(264 citation statements)
references
References 13 publications
11
253
0
Order By: Relevance
“…Such a function could be fluid flow sensing [54]. In support of this hypothesis, it has been shown that mechanical bending of the primary cilium or fluid flow in MDCK cells resulted in increases in intracellular Ca 2+ concentration which was dependent on extracellular Ca 2+ , PLC activation and inositol 1,4,5 trisphosphate (IP 3 )-induced release of intracellular Ca 2+ stores [55][56][57]. It is noteworthy that bending-induced Ca 2+ signaling was not affected by inhibition of ryonodine receptors [55].…”
Section: Function At the Primary Ciliummentioning
confidence: 91%
“…Such a function could be fluid flow sensing [54]. In support of this hypothesis, it has been shown that mechanical bending of the primary cilium or fluid flow in MDCK cells resulted in increases in intracellular Ca 2+ concentration which was dependent on extracellular Ca 2+ , PLC activation and inositol 1,4,5 trisphosphate (IP 3 )-induced release of intracellular Ca 2+ stores [55][56][57]. It is noteworthy that bending-induced Ca 2+ signaling was not affected by inhibition of ryonodine receptors [55].…”
Section: Function At the Primary Ciliummentioning
confidence: 91%
“…In mice lacking P2X 4 receptors, flowinduced increases of [Ca 2+ ] i in the endothelial cells were absent, as was the endothelium-dependent vascular dilatation. Flow-induced increases in [Ca 2+ ] i can also be elicited in renal epithelia [130][131][132]. This phenomenon has received much attention as it was hypothesised that an absence of flow sensing in renal epithelia causes polycystic kidney disease [133].…”
Section: Mechanically Released Nucleotidesmentioning
confidence: 99%
“…Primary cilia were removed from CHEC essentially as was described before (Praetorius and Spring, 2003). In short, CHEC were treated for 72 hr with 5ϫ10 -3 Mol/L Chloral Hydrate (Sigma) in tissue culture medium to remove cilia, followed by 24 hr recovery in standard medium.…”
Section: Removal Of Endothelial Cilia In Vitromentioning
confidence: 99%